(3GdEbdjO aj TQM GdeaUds - (3JGL GdOjf CMeO Hf eMehO Hf YeQ GdNLfOj, GdNLfOj,J (B700 (3g` s ((3eMeO Hf MSGe MGaX GdeJNP GdMhGQi s)
(3ChdgG (B:s
(3EjGg CMeO Ydi fYe JgddJ hLhgG GdUHGM s
(3BNQgG (B:s
(3aQZ ef cJGHI cJGH TQM GdeaUd GdehShe HGdEbdjOq s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B305s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdfMhs